International Education and the Internationalization of Public Schooling in Canada: Approaches and Conceptualizations - Elnagar, Abdelhady; Young, Jon (Canadian Journal of Educational Administration and Policy / Revue canadienne en administration et politique de l’éducation)

(untitled) (Department of Educational Administration, University of Saskatchewan, 2021)
While there is now an extensive literature related to the internationalization of post-secondary education in Canada, developments within K-12 public schooling have received much less attention. This article explores recent developments in international education in Canadian public school systems, with specific attention to developments in Manitoba. In doing so it argues that these developments incorporate three distinct policy interests – trade, immigration and education – resulting in strong federal influences on provincial education policies and practices. The article examines two major international education initiatives: the recruitment of international students; and, the establishment of affiliate school agreements overseas. It argues that these recent developments reflect a particular notion of “the internationalization of public schooling” where a historical notion of “international education” as a learning-focused concept has been supplanted by an economic and market-driven notion that has trade and immigration considerations as its primary interests.